Prinsip-Prinsip dan Kerangka Dasar Pengembangan Kurikulum Pendidikan Agama Islam Di Sekolah Menengah Atas - Audi Sifah Karimah; Amal Khayati (PT. Nawa Edukasi Nusantara, 2025)
The development of the Islamic Religious Education (PAI) curriculum plays a strategic role in addressing the challenges of the digital era, character crises, and the increasingly complex currents of globalization. The PAI curriculum functions not only as a guide for religious learning but also as an instrument for shaping students who are faithful, virtuous, and capable of adapting to modern socio-cultural dynamics. This study employs a literature review method, analyzing various theories, policies, and previous research relevant to the development of the PAI curriculum at the secondary school level. The findings indicate that an ideal PAI curriculum should be grounded in Islamic philosophical values, take into account students’ psychological aspects, and consider the social context of the community. Moreover, it must integrate 21st-century competencies with Islamic moral values to achieve balance across cognitive, affective, and psychomotor domains. The main challenges in implementing the PAI curriculum include teacher preparedness, limited educational resources, and the paradigm shift toward learner-centered and character-based approaches. Therefore, continuous teacher training, the development of contextual digital learning materials, and authentic assessment systems are essential. These efforts are expected to create a PAI curriculum that is relevant, innovative, and effective in shaping Muslim students with strong character and global competitiveness.